The circulation of kinesic knowledge and its representation in the practice of Chinese martial arts : Body movements as traditions, sports and collective imagery - Porchet, Pierrick (The Journal of the International Society of Chinese Health Practices, 2024)
At the crossroads of contemporary Chinese studies, martial arts studies and the anthropology of the body, this doctoral thesis reflects on body movements and technical knowledge of Chinese martial arts today. Its guiding idea is that the complex issues linked to the transmission of these traditional practices, their institutional reinterpretation and their influence on the collective imagery can be traced back in the materiality of practitioners' bodies and their movements. Based on an analysis of the circulation of kinesic knowledge through various frameworks of practice in China today, this research is divided into four parts: a theoretical reflection on the broad notion of embodiment and its application in the Social sciences and Humanities; an inventory of the major categories that define the Chinese martial arts; two studies that describe, mainly in the form of ethnographic observations, both traditional and sport practices observed in China; a reflection on the collective imagery linked to martial arts and how this can be interpreted today.